2007
DOI: 10.1134/s0006297907030121
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of coenzyme Q10 limits postinfarct myocardial remodeling in rats

Abstract: The effect of chronic coronary artery occlusion on the content of rat myocardial coenzymes Q (CoQ) and evaluation of the applicability of CoQ(10) for limiting postinfarct remodeling have been investigated. Left ventricle myocardium hypertrophy was characterized by the decrease in CoQ(9) (-45%, p < 0.0001), CoQ(10) (-43%, p < 0.001), and alpha-tocopherol (-35%, p < 0.05). There were no differences between the parameters of postinfarction and sham-operated rats in plasma. Administration of CoQ(10) (10 mg/kg) via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
17
0
2
Order By: Relevance
“…Экстракцию CoQ 10 из плазмы крови проводили по методике Lass и Sohal [13] с небольшими изменениями [14]. К плазме крови добавляли этанол и n-гексан (1:2:5), тщательно встряхивали в течение 10 мин, центрифугировали (4000 g) в течение 3 мин и отбирали верхний слой n-гексана.…”
Section: анализ Coq 10 в плазме кровиunclassified
“…Экстракцию CoQ 10 из плазмы крови проводили по методике Lass и Sohal [13] с небольшими изменениями [14]. К плазме крови добавляли этанол и n-гексан (1:2:5), тщательно встряхивали в течение 10 мин, центрифугировали (4000 g) в течение 3 мин и отбирали верхний слой n-гексана.…”
Section: анализ Coq 10 в плазме кровиunclassified
“…This is in line with published data indicating that plasma concentrations of coenzyme Q 10 are 2-2.5 times higher during long-term oral therapy with solubilized forms [4] and the bioavailability is 3-6 times higher in comparison with powder [6,12]. The pharmacokinetic advantages of solubilized form are responsible for its high efficiency as a cardioprotector: chronic oral treatment led to an increase of not only plasma levels of coenzyme Q 10 (2.5 times), but of also its concentration in rat myocardium, which improved survival of cardiomyocytes under conditions of ischemia and eventually limited the size of the postinfarction necrotic zone [2].…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic curves of coenzyme Q 10 concentrations, mean for groups, for solubilized form (1) and powder(2). *p<0.00001, **p<0.001, ***p<0.05 compared to 2.…”
mentioning
confidence: 99%
“…In a Study, solubilized coenzyme Q10 has shown better absorption, higher plasma concentration, and consequently better bioavailability which indicates that plasma concentrations of coenzyme Q10 are 2-2.5 times higher during long-term oral therapy with solubilized forms and the bioavailability is 3-6 times higher comparing with powder. (27)(28)(29)…”
Section: Biochemistry In the Humanmentioning
confidence: 99%